The Response of the GMIM Golgota Bukit Ranomuut Permai Congregation to Mental Health Issues: Tanggapan Jemaat GMIM Golgota Bukit Ranomuut Permai Mengenai Isu Kesehatan Mental - Lea Lembong; Terry Lalogiroth; Yovan Pusung; Gloria Damongilala; Denny Adry Tarumingi; Linda Patricia Ratag; Ineke Marlien Tombeng; Mieke Nova Sendow (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to analyze the perceptions, attitudes, and responses of the congregation of GMIM Golgota Bukit Ranomuut Permai toward mental health issues, as well as to identify the theological, social, and cultural factors shaping those responses. Using a descriptive qualitative approach with purposive sampling techniques, the research involved 26 participants drawn from church ministers (Pelsus), youths, and general congregants, selected through an open online questionnaire. The data were analyzed thematically and validated through source triangulation. The findings indicate that 96.2% of respondents had previously heard about mental health issues, reflecting a high level of awareness. However, 65.4% reported having experienced stress, anxiety, or depression in recent months, even though access to professional services remains hindered by limited knowledge (12 mentions) and fear of social stigma (8 mentions). Although 65.4% of respondents were aware of the existence of mental health services, one-third still lacked understanding of how to access them. Suggested interventions from the congregation include routine educational programs in the church, the provision of free consultations, the establishment of support groups, the cultivation of a listening culture, and structured spiritual accompaniment. The study reveals a gap between awareness and action, influenced by religious stigma and limited information. It recommends integrating mental health literacy into pastoral ministry, establishing a pastoral referral system, and fostering collaboration between the church and professional practitioners. The church is positioned as an agent of social transformation capable of providing a safe space for holistic healing—physical, psychological, and spiritual—within the framework of a theology of shalom. This research offers practical contributions to the development of contextual pastoral care and enriches academic discourse on the intersection of religion, culture, and mental health in Indonesia.